Navigating the Digital Shift: Key Drivers of Zakat Reporting Effectiveness in Indonesia - Aisha Putrina Sari; Syifa Aziza; Yuna Adeptia; Igres Ariresa; Ahmad Fauzi; Syukri Yandi; Iklimah Dalhudah (Universitas Islam Internasional Indonesia, 2026)
Digital transformation in zakat reporting is essential to enhance transparency, accountability, and efficiency in managing zakat, infaq, and sadaqah in Indonesia. Indonesia’s National Zakat Board (BAZNAS) developed the Zakat Information Management System (SIMBA) system to support standardized, real-time reporting across national and regional zakat institutions. However, adoption remains limited due to challenges such as low digital literacy, insufficient technical infrastructure, and organizational readiness gaps, especially in Eastern Indonesia. This study identifies key factors influencing the implementation of SIMBA and provides a model to improve compliance in digital zakat reporting in Indonesia. Using the Analytic Hierarchy Process and Multi-Stage Weighted Index method, the study analyzes data from 207 respondents, including experts and practitioners from BAZNAS and zakat management institutions. The findings highlight six critical dimensions affecting SIMBA’s adoption: organizational readiness, ease of use, compliance and regulation, user attitudes and perceptions, external factors, and motivation and incentives. Organizational readiness emerged as the most influential factor, followed by technological usability and institutional motivation. The study concludes that effective SIMBA implementation requires strong leadership, technical support, and structured incentives. These insights can help close the digital gap in zakat reporting and ensure Indonesia’s zakat ecosystem is transparent and accountable.